2018
DOI: 10.3390/met8010031
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic Milling of Titanium Powder

Abstract: Ti Grade 2 was prepared by cryogenic attritor milling in liquid nitrogen and liquid argon. Two types of milling balls were used-stainless steel balls and heavy tungsten carbide balls. The effect of processing parameters on particle size and morphology, contamination of powder and its microhardness was investigated. Milling in liquid nitrogen was not feasible due to excessive contamination by nitrogen. Minor reduction of particle size and significant alterations in particle morphology depended on type of millin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…It was found that titanium remains ductile even at cryogenic temperatures (unless contaminated by nitrogen [21]) and powder particles are not significantly refined [22]. On the other hand, powder particles are significantly deformed by repetitive plastic deformation [15,22,23]. In our previous study we proved that deformation by ball milling resembles the multi-directional forging and causes grain refinement [24].…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…It was found that titanium remains ductile even at cryogenic temperatures (unless contaminated by nitrogen [21]) and powder particles are not significantly refined [22]. On the other hand, powder particles are significantly deformed by repetitive plastic deformation [15,22,23]. In our previous study we proved that deformation by ball milling resembles the multi-directional forging and causes grain refinement [24].…”
Section: Introductionmentioning
confidence: 90%
“…Cryogenic milling employing the Szegvari type attritor has been previously applied to commercially pure titanium [18][19][20][21]. It was found that titanium remains ductile even at cryogenic temperatures (unless contaminated by nitrogen [21]) and powder particles are not significantly refined [22]. On the other hand, powder particles are significantly deformed by repetitive plastic deformation [15,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations